2009
DOI: 10.1080/00207170902838269
|View full text |Cite
|
Sign up to set email alerts
|

Consensus problems in networks of agents with double-integrator dynamics and time-varying delays

Abstract: In this article, we consider consensus problems in networks of agents with double-integrator dynamics and non-uniform time-varying delays. The agent dynamics is adopted as a typical point mass model based on Newton's law. Without assuming that the weighting factors in the information update schemes are non-negative, we propose two protocols such that both the state and the velocity of agents achieve consensus. An equivalent reduced-order system is introduced to analyse the convergence of the protocols. Some ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(65 citation statements)
references
References 21 publications
0
65
0
Order By: Relevance
“…Owing to the complexity of the non-linearity, the existing linear consensus methods, such as [12][13][14][15][16][17], cannot be directly applied to non-linear systems. In recent years, several scholars have addressed the non-linear consensus problem [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the complexity of the non-linearity, the existing linear consensus methods, such as [12][13][14][15][16][17], cannot be directly applied to non-linear systems. In recent years, several scholars have addressed the non-linear consensus problem [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…So the second-order agreement is more challenging, and can be more widely applied to real systems. In recent decades, many eminent research results about linear second-order consensus control have been published [12][13][14][15][16][17], where [12,13] for leaderless consensus and [14-17] for leader-following consensus.In reality, most multi-agent system dynamics contain the intrinsic non-linearity. Owing to the complexity of the non-linearity, the existing linear consensus methods, such as [12][13][14][15][16][17], cannot be directly applied to non-linear systems.…”
mentioning
confidence: 99%
“…Let the Lyapunov functionals defined by (12) and (13) be the common Lyapunov functional for the switched System (21), respectively. Then, similar to the analysis in Theorem 1 and Corollary 1, we get the following consensus results for the case of switching topology.…”
Section: Remark 3 Unlike Most Of the Consensus Analysis For Multi-agmentioning
confidence: 99%
“…[1][2][3][4][5]. Consensus seeking has been analyzed mainly for first-order multi-agent systems modeled by a single integrator [6][7][8][9][10][11] and second-order multi-agent systems modeled by double integrators [12][13][14], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For example, consensus was examined for multi-agent systems with general linear dynamics in Li et al (2007), Seo et al (2009). In Ren and Beard (2008), Sun and Long (2009) consensus problems for agents with single/double or higher integrator dynamics were studied. In Fax and Murray (2004), the authors focused on the stabilisation of a network of identical agents with linear dynamics whilst in Cai et al (2011) the authors suggested necessary and sufficient conditions for swarm stability of high-order linear time-invariant (LTI) multi-agent systems.…”
Section: Introductionmentioning
confidence: 99%